2014
DOI: 10.1007/s12185-014-1713-9
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of concurrent development of essential thrombocythemia with chronic lymphocytic leukemia, one related to clonal B-cell lymphocytosis, tested by array comparative genomic hybridization

Abstract: We present two cases of concurrent development of essential thrombocythemia (ET) with chronic lymphocytic leukemia (CLL) and one related to clonal B-cell lymphocytosis (CBL). Both patients were referred for lymphocytosis and thrombocytosis. A bone marrow biopsy revealed infiltration of small, mature lymphocytes and megakaryocytic hyperplasia. Flow cytometric immunophenotyping and immunoglobulin (IG) gene clonality tests revealed clonal B lymphocytes. Both patients were positive for the JAK2 V617F mutation in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…It should be noted that the gene-expression analyses using sorted bulk CLL cells did not show significant differences in the expression of BACH2, RELB, NF-kB2, and NOTCH1 between CLL cells from patients with or without concurrent AML (supplemental Figure 3D), suggesting that future studies using combined transcriptomic and gene mutation analysis at the single-cell level are required to further characterize this subpopulation and determine whether they have greater potential to convert to the myeloid lineage. Although our somatic mutational analyses clearly demonstrate the existence of common lymphoid and myeloid leukemia progenitors and are consistent with some previous studies, 23,24 we recognize that not all reported cases show a clonal relationship by targeted gene sequencing between concurrent or sequentially developed lymphoid and myeloid tumors. 25 However, analysis of these types of cases using WES may be more informative, as evidenced by the cases presented here.…”
Section: Cll Cells Convert To Myeloid Lineage In Vivosupporting
confidence: 91%
“…It should be noted that the gene-expression analyses using sorted bulk CLL cells did not show significant differences in the expression of BACH2, RELB, NF-kB2, and NOTCH1 between CLL cells from patients with or without concurrent AML (supplemental Figure 3D), suggesting that future studies using combined transcriptomic and gene mutation analysis at the single-cell level are required to further characterize this subpopulation and determine whether they have greater potential to convert to the myeloid lineage. Although our somatic mutational analyses clearly demonstrate the existence of common lymphoid and myeloid leukemia progenitors and are consistent with some previous studies, 23,24 we recognize that not all reported cases show a clonal relationship by targeted gene sequencing between concurrent or sequentially developed lymphoid and myeloid tumors. 25 However, analysis of these types of cases using WES may be more informative, as evidenced by the cases presented here.…”
Section: Cll Cells Convert To Myeloid Lineage In Vivosupporting
confidence: 91%
“…25 Thus, our study adds clarity to the apparent contradictory results from previous studies of patients with concurrent MPN/LPD: distinct clonal origins were suggested in a study of X-inactivation pattern in 3 females with MPN and CLL, 18 whereas other reports have found that JAK2 mutations can be detected in LPD cells in a subset of patients. 1,[19][20][21] Our findings suggest that the pathogenic processes underlying concurrent MPN/LPD can vary between patients. In some cases (as observed in patient B), the 2 disease clones originate independently and environmental factors or a germ-line predisposition state likely drive their parallel development.…”
mentioning
confidence: 71%
“…To address this hypothesis, detailed genetic characterization of patients with concurrent MPN/LPD is required; prior reports have exclusively focused on JAK2 or CALR MPN driver mutations, with the majority showing no contribution to lymphoid disease. 1,4,[14][15][16][17][18][19][20][21][22] Here, we analyzed 3 patients diagnosed with both myelofibrosis (MF) and a mature B-cell LPD; their clinical features are summarized in Table 1 and supplemental Figure 1 (available on the Blood Web site). All biological samples used in this study were collected in accordance with the Research Ethics Board of the University Health Network (REB#01-0573 and REB#02-0763).…”
mentioning
confidence: 99%
“…Ph-neg. CMPD és CLL (ritkábban monoklonális B-sejtes lymphocytosis) társulására újabb irodalmi adatok is utalnak [34][35][36][37][38]. Masarova és mtsai az MD Anderson Cancer Center (Houston, Amerikai Egyesült Államok) 1960-2014 kö-zötti betegdokumentációját áttekintve 9866 Ph-neg.…”
Section: Eredeti Közleményunclassified